2015
DOI: 10.1111/cdoe.12152
|View full text |Cite
|
Sign up to set email alerts
|

Oral health impacts on self‐rated general and oral health in a cross‐sectional study of working age adults

Abstract: For working age adults, oral health impact was associated with general health for those with more health problems indicating those in worse health suffer more impact from oral health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
3
27
0
3
Order By: Relevance
“…In a population aged 60‐71 years in South Australia, Brennan, and Singh reported that tooth loss was associated with poorer general health after adjusting for other covariates . Among adults aged 30 and 61 years in a nationally representative sample in Australia, Brennan, and Teusner reported that general health [as assessed by EuroQoL (EQ‐5D)] was worse when both the number of general health problems and adverse impacts of the mouth on daily life were high . Similar associations have been reported with orofacial pain .…”
Section: Introductionmentioning
confidence: 56%
“…In a population aged 60‐71 years in South Australia, Brennan, and Singh reported that tooth loss was associated with poorer general health after adjusting for other covariates . Among adults aged 30 and 61 years in a nationally representative sample in Australia, Brennan, and Teusner reported that general health [as assessed by EuroQoL (EQ‐5D)] was worse when both the number of general health problems and adverse impacts of the mouth on daily life were high . Similar associations have been reported with orofacial pain .…”
Section: Introductionmentioning
confidence: 56%
“…In another study, the differences in the OHIP-14 mean scores between the levels of SES were approximately two scores, which may be considered a small difference in relation to subjective and objective aspects of health and well-being (23). Thus, previous studies have shown a relationship between the OHIP-14 and SES (21,24,25), but, to our knowledge, the literature lacks information about the OHIP-5 with different reference norms in relation to indices of social determinants.…”
Section: Discussionmentioning
confidence: 94%
“…For the comprehension of the healthdisease process and considering the perspective that oral health is related to social determinants of health, it is necessary to further explore this issue in specific populations, such as university students, as such approaches can influence general health 17 and the capacity for work 18 and can be measured using an instrument validated for use in Brazil -the short-form Oral Health Impact Profile (OHIP-14)…”
Section: Introductionmentioning
confidence: 99%